2009
DOI: 10.1007/s00192-009-0954-2
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence and detrusor dysfunction associated with pelvic organ prolapse: clinical value of preoperative urodynamic evaluation

Abstract: Preoperative urodynamic evaluation of SUI and detrusor function was useful for predicting postoperative urinary conditions in POP patients. Its cost-effectiveness remains to be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 28 publications
3
53
1
Order By: Relevance
“…The study showed the cough stress test to be sufficient for the diagnosis of occult SUI, the presence of DO was a good predictor of persistent postoperative urgency and UUI. Furthermore, the study showed that poor detrusor contractility during preoperative urodynamics predicts large postoperative PVR [26].…”
Section: Pelvic Organ Prolapsementioning
confidence: 87%
“…The study showed the cough stress test to be sufficient for the diagnosis of occult SUI, the presence of DO was a good predictor of persistent postoperative urgency and UUI. Furthermore, the study showed that poor detrusor contractility during preoperative urodynamics predicts large postoperative PVR [26].…”
Section: Pelvic Organ Prolapsementioning
confidence: 87%
“…This was similar to the procedure evaluated by Meschia et al 21 and Gordan D et al 20 In our study we utilized the transobturator polypropylene mesh as midurethral sling. This technique of sling placement was similar to the procedure undertaken by Araki et al 22 who performed transobturator midurethral sling placement only in patients with symptomatic SUI and/or positive cough test along with repair of POP by polypropylene mesh. 18 who also reported a significant difference of SUI at 12 months post surgery (p <0.001).…”
Section: Proceedings In Obstetrics and Gynecology 2017;7(1):6mentioning
confidence: 96%
“…[13][14][15][16] Several studies have been conducted to assess the benefits and effects of a prophylactic sling surgery. Various studies have evaluated this in the context of abdominal surgery, for example, Burch colposuspension 7,8 and vaginal procedures, such as, transvaginal tape [18][19][20][21] and transobturator tape 22 approach. To the best of our knowledge, no such study has been conducted in India.…”
Section: Prophylactic Midurethral Slingmentioning
confidence: 99%
“…The presence of DO on preoperative UDS in this series was a significant predictor of postoperative persistence of urgency or UUI; of note, 31% of patients with urgency had DO on UDS. Concurrent performance of transobturator tape was not associated with postoperative persistence of urgency/UUI or development of de novo urgency [28]. An earlier report from Basu and Duckett [29] used urodynamic data to study potential factors contributing to improvement of OAB after prolapse surgery.…”
Section: Surgical Repair Of Pelvic Organ Prolapsementioning
confidence: 97%
“…These changes were not significantly correlated with age, parity, body mass index, grade of prolapse, or presence of DO on UDS. Persistent urgency incontinence was significantly, although very modestly (OR, 1.056), related to higher preoperative detrusor pressure at maximum flow rate [ Araki et al [28] studied the correlation of preoperative urodynamics on postoperative symptoms in 87 women who underwent transvaginal mesh surgical repair for POP with or without concomitant suburethral sling. Six months postoperatively, urgency resolved in 25 (52%) of 48 and UUI resolved in 18 (69%) of 26 patients.…”
Section: Surgical Repair Of Pelvic Organ Prolapsementioning
confidence: 99%